On the problem of interethnic situation in the Udmurt Republic - S N Uvarov; S V Kozlovsky (RUDN journal of Sociology, 2014)
The article is devoted to the current state of interethnic relations in the Republic of Udmurtia. Considering the population perception of labor migrants from other ethnic groups, the authors identify the key problems in the sphere of interethnic communication and reasons for intolerant behavior, suggest some ways to reduce tensions in everyday social interaction.